2005
DOI: 10.1021/es049553q
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Compound-Specific Isotope Analysis Method for Atmospheric Formaldehyde and Acetaldehyde

Abstract: A novel method determining compound-specific carbon isotopic compositions for atmospheric formaldehyde and acetaldehyde in ppb or sub-ppb levels by gas chromatography/ combustion/isotope ratio mass spectrometry (GC/C/ IRMS) is presented. Atmospheric carbonyls are collected using the conventional 2,4-dinitrophenylhydrazine (DNPH) derivatization method, and their delta13C values are calculated based on stoichiometric mass balance after measuring the carbon isotopic compositions of the carbonyl-DNPH derivatives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 23 publications
5
51
3
Order By: Relevance
“…In such a closed environment, vehicle emission was the main source of atmospheric pollutants. It was the same for HCHO, which was proved by the accordance of carbon isotopic data of atmospheric HCHO (close to À20&, Wen et al, 2005) and vehicle emitted HCHO (this study).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In such a closed environment, vehicle emission was the main source of atmospheric pollutants. It was the same for HCHO, which was proved by the accordance of carbon isotopic data of atmospheric HCHO (close to À20&, Wen et al, 2005) and vehicle emitted HCHO (this study).…”
supporting
confidence: 83%
“…Furthermore, isotopic composition measurement can also be used to assess the flux of many atmospheric compounds (Goldstein and Shaw, 2003;Wang et al, 2012). In previous studies, carbon isotopic compositions of ambient HCHO in different sites were reported, and the primary results showed that carbon isotopic analysis could provide some valuable information for better understanding of the sources of HCHO in ambient air (Brenninkmeijer et al, 2003;Johnson and Dawson, 1990;Rice and Quay, 2009;Tanner et al, 1996;Wen et al, 2005). However, information on the isotopic signature of the sources needed for interpretation of atmospheric HCHO is limited (Guo et al, 2009;Wen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This rapid growth in vehicle number makes vehicle exhaust an increasingly important contributor to air pollutants including carbonyls Wen et al, 2005;Hu et al, 2014), particularly in the urban areas. To determine vehicle emission factors, road tunnels are excellent locations not only because the influence of meteorological conditions is minimized and the emissions undergo 'real world' dilution effect with minimal interference from other sources, but also because road tunnel tests provide emissions from a large number of vehicles operating at 'real world' hot and stable conditions when going through a road tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…With the possibility of incorporating the isotopic data, primarily carbon or hydrogen isotopic data (Macko and Parker 1983;Wang et al 2004;Glaser et al 2005;Wen et al 2005) and, in selected cases, chlorine, nitrogen, oxygen or sulfur isotopes (Sturchio et al 1998;Beneteau et al 1999;Reddy et al 2000;Coffin et al 2001;Shouakar-Stash et al 2003) many of these ambiguities can be eliminated.…”
Section: Source Discrimination or Correlationmentioning
confidence: 99%